PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC)BERBASISPEMECAHANMASALAH MODEL POLYA UNTUK MENINGKATKANAKTIVITAS DAN HASIL BELAJAR SISWA PADASUBPOKOK BAHASAN OPERASI HITUNG PECAHAN DI KELAS VII-DSMP NEGERI 2ARJASA - Pramono, Dwi Roby; Suharto, S; Kristiana, Arika Indah (KadikmA, 2014)
Abstract.The purpose of this researchis to helpsstudent to build their understanding about story termand up their problem solving. This research type of Classroom Actions Research (CAR) using Cooperative Integrated Reading and Composition model with Polyaâs method in fraction operations at VII-D grade of SMP Negeri 2 Arjasa. The research has two cycleswhich has devising a plan, action, observation, and reflection for each cycle.Data collected by documentation, observation, test and interview method. The data observation showed increasing about teacherâs activity and studentâs activity from 1st cycle to 2nd cycle. The studentâs learning in 1st cycle showed that 29 students completed and 11 students not completed. So, the classical completion results that class uncompleted with percentage 72,5%. But the studentâs learning result of 2nd cycle showed a good progress andclass completed with percentage 82,5%. KeyWords:Cooperative learning model using CIRC, Polyaâs method,teacherâs activitiy,studentâs activitiy,and studentâslearning result